2013
DOI: 10.3329/bvet.v29i2.14344
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacteria associated with omphalitis in chicks

Abstract: This study was conducted to isolate and characterize the bacteria present in cases of omphalitis in chicks. Yolk swabs (n = 60) were aseptically collected from affected chicks and cultured for isolation and identification of bacteria. E. coli, Salmonella and Staphylococci were identified. Bacteria were tested for sensitivity to ten common antibiotics. E coli isolates were sensitive to chloramphenicol and resistant to nalidixic acid, ampicillin, amoxycillin, ciprofloxacin, tetracycline, gentamicin, sulphamethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 6 publications
4
10
0
1
Order By: Relevance
“…species in collected samples of chick meconium (49) from hatchery and this findings was very close to the findings of several researchers (Nasrin et al, 2012). These findings also indicate that vertical transmission of Salmonella species occurred to the chick that was similar to the findings reported by several researchers (Cason et al, 1994;Bailey et al, 1994).…”
Section: Resultssupporting
confidence: 90%
“…species in collected samples of chick meconium (49) from hatchery and this findings was very close to the findings of several researchers (Nasrin et al, 2012). These findings also indicate that vertical transmission of Salmonella species occurred to the chick that was similar to the findings reported by several researchers (Cason et al, 1994;Bailey et al, 1994).…”
Section: Resultssupporting
confidence: 90%
“…The resistance of E. coli, Salmonella and S. aureus to multiple antimicrobials observed in this study supports the reports of previous works (Khan et al, 2002;Nasrin et al, 2012;Lee et al, 2005;Abadi et al, 2013). This may probably suggest the wide use of these antimicrobials for treatment of bacterial infections in both animals and humans as these bacteria are environmental contaminants from clinical cases.…”
Section: Disc Content (µG)supporting
confidence: 92%
“…The lamina propria and submucosa consisted of loose connective tissue. The tunica muscularis was strongly thick and constructed of parallel smooth muscle fibers covered by the outer serosa (Nasrin et al, 2012). There were paucity of work studied the histomorphological and histochemical structures of the mallard's stomach and to our knowledge there were no local studies yet.…”
Section: Introductionmentioning
confidence: 99%
“…The cavities converged to form a common duct that lead to the surface through the apex of a small papilla. The surface epithelium on the folds was a simple columnar tissue and each fold had a core of lamina propria to support it (Nasrin et al, 2012). Rossi et al (2005) observed in the gizzard's mucosa of the partridge (Rhynchotus rufescens) low folds lined by simple columnar to cuboidal epithelium.…”
Section: Introductionmentioning
confidence: 99%